MENGEKSPLORASI PENGARUH PRIOR OPINION DAN OPINION SHOPPING TERHADAP OPINI AUDIT GOING CONCERN DENGAN FINANCIAL DISTRESS SEBAGAI PEMODERASI - Alifah Rahmah Fitri; Akie Rusaktiva Rustam (Universitas Budi Luhur, 2024)
This study aims to empirically examine the effect of prior opinion and opinion shopping on a going concern audit opinion with financial distress as a moderation variable. The population includes transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022, from which the samples of 78 companies are selected through purposive sampling and analyzed by logistic regression analysis. The study results exhibit that prior opinion has a positive and significant effect on a going concern audit opinion. In contrast, opinion shopping does not significantly affect a going concern audit opinion. Financial distress does not moderate the effect of prior opinion and opinion shopping on a going concern audit opinion.